Chronic and acute alcohol administration induced neurochemical changes in the brain: comparison of distinct zebrafish populations - Chatterjee, Diptendu; Shams, Soaleha; Gerlai, Robert (Amino acids, 2014)
The zebrafish is increasingly utilized in the analysis of the effects of ethanol (alcohol) on brain function and behavior. We have shown significant population-dependent alcohol-induced changes in zebrafish behavior and have started to analyze alterations in dopaminergic and serotoninergic responses. Here, we analyze the effects of alcohol on levels of selected neurochemicals using a 2 × 3 (chronic × acute) between-subject alcohol exposure paradigm randomized for two zebrafish populations, AB and SF. Each fish first received the particular chronic treatment (0 or 0.5 vol/vol % alcohol) and subsequently the acute exposure (0, 0.5 or 1.0 % alcohol). We report changes in levels of dopamine, DOPAC, serotonin, 5HIAA, glutamate, GABA, aspartate, glycine and taurine as quantified from whole brain extracts using HPLC. We also analyze monoamine oxidase and tyrosine hydroxylase enzymatic activity. The results demonstrate that compared to SF, AB is more responsive to both acute alcohol exposure and acute alcohol withdrawal at the level of neurochemistry, a finding that correlates well with prior behavioral observations and one which suggests the involvement of genes in the observed alcohol effects. We discuss correlations between the current results and prior behavioral findings, and stress the importance of characterization of zebrafish strains for future behavior genetic and psychopharmacology studies.